Wendan decoction (Traditional Chinese medicine) for schizophrenia - Deng, Hongyong (Cochrane Database Syst Rev, 2017)
BACKGROUND: Wendan decoction (WDD) is one of the classical Chinese herb formulas used for psychotic symptoms. It is thought to be safe, accessible and inexpensive. OBJECTIVES: To investigate the effects of WDD for treatment of people with schizophrenia or schizophrenia‐like illness compared with placebo, antipsychotic drugs and other interventions for outcomes of clinical importance. SEARCH METHODS: We searched the Cochrane Schizophrenia Group's Trials Register (February 2016), which is based on regular searches of CINAHL, BIOSIS, AMED, Embase, PubMed, MEDLINE, PsycINFO, China biomedical databases group (SinoMed, CNKI, VIP, Wanfang) and clinical trials registries. There are no language, date, document type, or publication status limitations for inclusion of records in the register. We also inspected references of identified studies and contacted relevant authors for additional information. SELECTION CRITERIA: Randomised controlled trials with useable data comparing WDD with antipsychotics, placebo or other interventions for people with schizophrenia. DATA COLLECTION AND ANALYSIS: We extracted data independently. For binary outcomes, we calculated risk ratios (RR) and 95% confidence intervals (CIs), on an intention‐to‐treat basis. For continuous data, we estimated mean differences (MD) between groups and their 95% CIs. We employed a random‐effect model for analyses. We assessed risk of bias for included studies and created 'Summary of findings' tables using GRADE. MAIN RESULTS: We included 15 randomised trials (1437 participants) of WDD for schizophrenia. There was a high risk of performance bias within the trials but overall, risk for selection, attrition and reporting bias was low or unclear. Data showed WDD improved the short‐term global state of participants compared with placebo or no treatment (1 RCT n = 72, RR 0.53, 95% CI 0.39 to 0.73, low‐quality evidence). When WDD was compared with antipsychotic drugs, such as chlorpromazine or risperidone, no difference in short‐term global state of participants was observed (2 RCTs n = 140, RR 1.18 95% CI 0.98 to 1.43, moderate‐quality evidence) and mental state (total endpoint Positive and Negative Syndrome Scale (PANSS): 2 RCTs, n = 140, MD 0.84, 95% CI ‐4.17 to 5.84, low‐quality evidence). However, WDD was associated with fewer people experiencing extrapyramidal effects (EPS) compared with other treatments (2 RCTs 0/70 versus 47/70, n = 140, RR 0.02, 95% CI 0.00 to 0.15, moderate‐quality evidence). WDD is often used as an add‐on intervention alongside antipsychotics. When WDD + antipsychotic was compared to antipsychotic alone, the combination group had better global state (short‐term results, 6 RCTs, n = 684, RR 0.60, 95% CI 0.50 to 0.72, moderate‐quality evidence) and mental state (short‐term total endpoint PANSS: 5 RCTs, n = 580, MD ‐11.64, 95% CI ‐13.33 to ‐ 9.94, low‐quality evidence), fewer people with EPS (2 RCTs n = 308, RR 0.46, 95% CI 0.30 to 0.70, moderate‐quality evidence) and reduction of the mean use of risperidone (1 RCT n = 107, MD ‐0.70, 95% CI ‐0.87 to ‐0.53, low‐quality evidence). But, there was no effect on weight gain (1 RCT n = 108, RR 0.50, 95% CI 0.20 to 1.24, low‐quality evidence). When WDD + low‐dose antipsychotic was compared with normal‐dose antipsychotic alone, the combination again showed benefits for short‐term global state (7 RCTs n = 522, RR 0.69, 95% CI 0.51 to 0.93, moderate‐quality evidence), mental state (total endpoint PANSS: 4 RCTs n = 250, MD ‐9.53, 95% CI ‐17.82 to ‐1.24, low‐quality evidence), and fewer participants with EPS (3 RCTS n = 280, RR 0.29, 95% CI 0.16 to 0.51, moderate‐quality evidence). Across all comparisons, we found no data on outcomes directly reporting quality of life, hospital service use and economics. AUTHORS' CONCLUSIONS: Limited evidence suggests that WDD may have some positive short‐term antipsychotic global effects compared to placebo or no treatment. However when WDD was compared with other antipsychotics there was no effect on global or mental state, but WDD was associated with fewer adverse effects. When WDD was combined with an antipsychotic, positive effects were found for global and mental state and the combination caused fewer adverse effects. The available evidence is not high quality. Better designed large studies are needed to fully and fairly test the effects of WDD for people with schizophrenia.